THE USING OF PORTFOLIO INRAISING STUDENTS’ AWARENESS IN DEVELOPING AUTONOMY - Mallipa, Imelda (Universitas Papua Manokwari, 2016)
This study describes how the using of portfolio raise students’ awareness in developing autonomy on the second semester students of English Education based on their attempt to develop their reading comprehension in order to increase their English vocabulary and their interest in searching information though English articles.The participants learnt though the porfolio process that adapted from Yildrim (2013). The documentation of 30 students’ goal, articles, summarizes, evaluation and reflection on their portfolio was analyzed descriptively. The result shows that the using of portfolio in teaching reading comprehension for students who have low motivation and interest and are lack of English vocabulary is effective to help students gradually accept their roles in learning English and raise students’ awareness of their responsibility in learning process.